Fractal properties of periodic plasma waveguides - Lapshyn, V.I.; Zaginaylov, G.I.; Tkachenko, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 2001)
Fractal properties of periodic plasma waveguides are investigated in this article. It's shown that the Hausdorff dimension of model dispersion law is dH=1/2 and for the Trivelpicec-Gould waves dH=1/3. These values indicete on fractal properties of investigated spectra.